Analisis Tingkat Kesukaran dan Daya Pembeda Butir Soal Asesmen Madrasah Mata Pelajaran Fikih di MI Ma’arif Pejagoan Tahun Pelajaran 2023/2024 - Rofifah, Ika Rifa; Subarkah, Imam (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This research aims to determine the quality of Madrasah Assessment items for the Fiqh subject at MI Ma'arif Pejagoan. The research method used is quantitative descriptive techniques with data collection techniques through documentation. The data analysis technique used is calculating the level of difficulty test and the distinguishing power test. Data analysis was carried out using Microsoft Excel software. The data analyzed is in the form of results on the answer sheets of students who took part in the Madrasah Assessment for Jurisprudence subjects at MI Ma'arif Pejagoan. The results of the research showed that overall, of the 50 questions, there were 2 questions (4%) in the difficult category, 35 questions in the moderate (medium) category, and 13 (26%) in the easy category. Meanwhile, in terms of discriminating power, the number of items that have poor discriminating power (negatively marked) is 9 items (18%), the bad category is 13 items (26%), the fair category is 10 items (20%) , the good category is 17 questions (34%), and the very good category is 1 question (2%). Keywords: Analysis, Level of Difficulty, Differentiating Power